Examination of Forensic Reports Given by a University Hospital Department of Psychiatry - Ersoy, Mehmet Akif; Zeyfeoğlu, Yıldıray; Hancı, İsmail Hamit; Coşkunol, Hakan (The Bulletin of Legal Medicine, 1999)
This study aimed to report forensic reports of a university psychiatry department. So that comparison with similar other studies later on, will reveal possible extrapolations for standardization of the forensic decision process. Most of the cases were sent from the institutions in the university town and its vicinity. More than half of the cases (%58) were civil law cases. Appointment of a guardian, testamentary and contractual capacity and competence (%42) and criminal responsibility (%22.4) were the most often questions asked by judicial offices. It is noticed that in some cases, psychiatrists could hardly make a definite decisione. It ought to discussed what should be done in such difficult cases. Both psychiatrists and jurists should work on the language and communication problems between institutions. Comparison of the results of this study with similar ones will be very fruitful.Key words: Forensic psychiatry
Keywords: forensic psychiatry